The Maʿānī al-Ḥadīth Approach to Understanding Travel Without a Mahram - Muhamad Zaenal Abidin; A. Zainuri Ghazali (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
Hadiths concerning the prohibition of women traveling without a mahram are often understood textually, resulting in various social implications, particularly regarding women’s mobility in the modern context. This study aims to analyze the understanding of such hadiths through the maʿānī al-ḥadīth approach in order to uncover their meaning, context, and relevance to contemporary social realities. The research employs a qualitative method with a library research approach, using primary data from hadiths related to travel without a mahram found in authoritative hadith collections, particularly Ṣaḥīḥ al-Bukhārī, and supported by classical hadith commentaries and relevant scholarly literature. Data analysis is conducted through textual-linguistic, historical-contextual, and hermeneutical analyses, emphasizing the aspects of asbāb al-wurūd, tawārīkh al-mutūn, and the objectives of Islamic law (maqāṣid al-sharīʿah). The findings indicate that the prohibition in these hadiths is preventive and contextual in nature, with the primary objective of safeguarding women’s safety and dignity. In the contemporary context, the presence of a mahram may be understood functionally as a system of protection that aligns with the development of modern security measures and social regulations. This study concludes that the maʿānī al-ḥadīth approach enables a more contextual, humanistic, and relevant understanding of the hadiths without undermining the authority of the text or the fundamental principles of Islamic teachings.